The incidence of personality types on the language proficiency level of students from Practice Teaching II at the Foreign Language Department during the semester II-2015. - Ortiz González, Claudia Marcela; Torres de Mendoza, Carmen Elena; Cruz, Juan Carlos (San Salvador, El Salvador : Universidad de El Salvador, 2016)
The current study aimed to determine the relationship between the personality types and the general English proficiency level of EFL students of Foreign Languages Department at the University Of El Salvador. In order to accomplish this, a sample was taken from students currently enrolled in the two groups of Practice Teaching II, Semester II, 2015 in the fourth year of the English Language major in Teaching Option (Licenciatura en Idioma Inglés Opción Enseñanza). The reason behind the choosing of these courses for this research lies on the fact that these students have already finished their five intensive courses of English within the major and it provides the opportunity to measure the proficiency level in the English language they have acquired throughout the process. In addition, reaching a certain level of English proficiency has become a requirement for students of the English Language major in Teaching Option (Licenciatura en Idioma Inglés Opción Enseñanza) to be promoted to advanced teaching practice courses, namely English Practice I and II (Práctica Docente I y II). Thus, the importance of observing the correlation between their proficiency level and the factors that may affect it, which, in this particular research, are the individual personality types. As student population at the Foreign Languages Department increases, course group also grow larger, which reportedly leads to a lowered proficiency level in the English language among the student population due to inversely proportional personalized attention in the classroom. This is the main reason serving as motivation for this research. On the other hand, it is important to highlight that taking and passing the TOEFL test is one of the requirements from the Foreign Language Department for students to do their practices, and subsequently be placed in the different projects and programs available at the Foreign Languages Department, different faculties and schools at the University of El Salvador, and outside the main campus. Therefore, the level of proficiency is an important and decisive factor to become a teacher after finishing the major.
Incluye anexos.
Tesis para optar al titulo de (Licenciatura en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2016
Bibliografía : 75-77 hjojas
Audiencia general.
Keywords: Methods and Instruments of Data Gathering